2021
DOI: 10.3390/v13071213
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Update of Severe Fever with Thrombocytopenia Syndrome

Abstract: Severe fever with thrombocytopenia syndrome (SFTS) is an acute febrile illness characterized by fever, leukopenia, thrombocytopenia, and gastrointestinal symptoms such as diarrhea, nausea, and vomiting resulting from infection with the SFTS virus (SFTSV). The SFTSV is transmitted to humans by tick bites, primarily from Haemaphysalis longicornis, Amblyomma testudinarium, Ixodes nipponensis, and Rhipicephalus microplus. Human-to-human transmission has also been reported. Since the first report of an SFTS patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(80 citation statements)
references
References 119 publications
0
80
0
Order By: Relevance
“…A survey by the Ministry of the Environment reported that the habitat area of Japanese deer and wild boars was mainly West Japan, although the area had been spreading northward every year [ 17 , 18 , 19 , 20 ]. A previous study concluded that wildlife habitat area changes also accelerated the spread of infection of Japanese spotted fever and scrub typhus, both of which are related to ticks [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A survey by the Ministry of the Environment reported that the habitat area of Japanese deer and wild boars was mainly West Japan, although the area had been spreading northward every year [ 17 , 18 , 19 , 20 ]. A previous study concluded that wildlife habitat area changes also accelerated the spread of infection of Japanese spotted fever and scrub typhus, both of which are related to ticks [ 21 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the numbers of patients received concervative treatment including fluid transfusion, and administered antiviral drugs were significantly higher in the group that was still alive. Previous studies have reported that there was limited evidence supporting active treatment, whereas conservative treatment administered appropriately was the most critical course of action [ 7 , 17 ]. There have been discrepancies between Japan and other Asian countries in diagnosing SFTS and in collecting data related to its prognosis and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Around 36 COVID-19 patients had taken 400 mg umifenovir three times per day for nine days in a clinical pilot project in Wuhan, China, with 31 uncontrolled COVID-19 patients taking part as a control condition. When compared with the control group, umifenovir therapy was found to have a higher proclivity for reducing viral load as determined by RT-PCR, and also a reduced fatality rate of 0% vs. 16% [ 111 ]. Table 1 illustrates some combinational drugs that can act as potential targets for COVID-19.…”
Section: Therapeutic Approach Against Covid-19mentioning
confidence: 99%
“…A number of zoonotic and non-zoonotic viruses have the potential to create pandemics. These viruses include human Metapneumo virus (hMPV), Respiratory syncytial virus (RSV), severe fever with thrombocytopenia syndrome virus (SFTSV), Hanta virus (HTNV), Sin Nombre virus (SNV), avian Influenza A strain (H7N9), Ebola virus, Zika virus, Nipah virus, Hepatitis viruses, West Nile fever virus, Lujo virus, Lassa virus (LASV), Dengue virus (DENV), and Chikungunya virus (CHIKV), to name only a few [5][6][7][8]. One point to note is that these viruses are, on top of other 'common' viruses like Human immunodeficiency virus (HIV) and human Papilloma virus (HPV), currently infecting millions of people, but not attracting a great deal of general attention, probably because they have been around for some time and at least some forms of treatment are now available for them [9].…”
Section: Introductionmentioning
confidence: 99%